Islamic Law Reform: Achieving Grace through Tahlil & Tawasul - Caswito; Yahya Zainul Muarif; Abdul Aziz (Universitas Islam Indonesia, 2024)
The study's originality lies in its balanced approach to the highly debated practices of tahlil and tawasul within Indonesian society. Unlike previous works that often align strictly with these practices' legalistic critique or cultural defense, this research comprehensively explores these practices, integrating legal and societal perspectives. By employing a qualitative, descriptive exploratory method supported by an extensive literature review, the study goes beyond the surface-level debates to uncover the more profound cultural and social significance of tahlil and tawasul. The study fills a gap in the existing literature by addressing the lack of nuanced discourse on these practices, particularly regarding their evolution from religious rituals associated with death to broader expressions of local wisdom and community bonding. It offers a fresh perspective on how these practices can be understood as religious customs and vital elements of social cohesion and cultural identity in Indonesia. Furthermore, the study bridges the divide between opposing views by advocating for mutual respect and recognizing tahlil and tawasul as part of the rich tapestry of Islam in the country. This approach contributes to the ongoing conversation about the role of local traditions in Islamic practice, promoting a more inclusive understanding that acknowledges the diversity of religious expression within the Muslim community.